Assessment of the environmental quality of Lake Skadar and its urban surroundings in Montenegro - Dragan Burić; Ivan Mijanović; Miroslav Doderović; Jovan Mihajlović; Goran Trbić (European Journal of Geography)
Lake Skadar on the Balkan Peninsula faces many ecological challenges. The lake is located in the border area between Montenegro and Albania and its ecosystem interacts with important and highly populated urban centres such as Podgorica and Bar. Despite the crucial role the lake plays in the sustainability of the ecosystem and the health of the population, there is a lack of environmental quality assessment and data-based analysis. Therefore, the aim of this study is to assess both the water quality of Lake Skadar and the air pollution in Podgorica and Bar in the period from 2011 to 2018. To assess water quality, the Water Quality Index (WQI) model, i.e. the SWQI method, was used, which was calculated based on 10 parameters of physicochemical and microbiological characteristics of water from 9 hydrological stations (oxygen saturation, biochemical oxygen consumption for 5 days, ammonium ions, pH, total nitrogen oxides, orthophosphates, suspended solids, temperature, electrical conductivity and coliform bacteria). In addition, air quality in the two cities was assessed using timeseries of PM10 concentrations. The results showed that the water quality of Lake Skadar was of good to high quality (WQI 79-95), while the air quality in Podgorica and Bar was a serious public health problem, especially in the cold seasons in Podgorica (i.e. the average seasonal and daily PM10 concentrations were often > 40 and > 50 µg/m3). These results are of great practical importance for environmental management and support decision makers in applying certain environmental protection measures and strategies.